Generation and utility of cyclic dienyl gold carbene intermediates - Zhang, Cheng; Hong, Kemiao; Dong, Shanliang; Liu, Mengting; Rudolph, Matthias; Dietl, Martin C.; Yin, Jian; Hashmi, A. Stephen K.; Xu, Xinfang (ACS catalysis, 2023)
Exploration of intermediates that enable chemo- and stereoselective cycloaddition reactions for the expeditious construction of fused- and bridged-ring systems continues to draw a great deal of interest from the synthetic community. Vinylcarbene intermediates, which serve as 1- or 3-carbon building blocks, have been frequently used for the construction of cyclic frameworks through the successive formation of multiple carbon-carbon or/and carbon-heteroatom bonds. Here, we present a concise strategy for the catalytic generation of cyclic dienyl gold carbene species (Au-CDC) via a selective gold-promoted diazo-enyne carbocyclization process. Following cycloadditions of these in situ formed carbene intermediates with different types of dipolarophiles are disclosed, producing a diverse array of fused and bridged skeletons with high chemo- and stereoselectivity. This method provides a tool resulting in straightforward access to ring systems with structural complexity and diversity, and is a substantial complementary protocol to existing methods relying on using open-chained vinylcarbene species. The subsequent exploration of these generated cyclopentadiene motifs with dipolarophiles in accessing targets of polycyclic structures can further increase this rings-per-operation count, leading conceptually to the Au-CDC as a key bridge capable of connecting back-to-back cycloadditions.